PERJANJIAN SEWA GUNA USAHA DAN PENGUASAAN GROSSE AKTE KAPAL DENGAN HAK OPSI MEMBELI - Mufrina, Mufrina; Sufiarina, Sufiarina (CV. AFDIFAL MAJU BERKAH, 2024)
The Lease Purchase Agreement operated by the financing company involves the provision of capital goods for the lessee's benefit. The lessor provides facilities for the procurement of capital goods that are delivered to the lessee for a specified period, with the obligation to make periodic payments. In a lease-purchase agreement, the lessor acts as the owner, and the goods are in the possession of the lessee. At the end of the lease period, the lessee is given the option to extend the lease term or exercise the right to purchase the leased capital goods. Since the capital goods belong to the lessor, it is not possible to use the leased object as collateral in the financing agreement. Ownership of the leased object with the option to buy should occur at the end of the lease agreement. However, in the Lease Purchase Agreement with Reference Number PPAF/PSGUP/2014/VIII/133, the lessee has become the owner of the capital goods from the beginning, both in physical and legal terms, because the capital goods were transacted through a notarial deed and registered under the lessee's name with the harbor master's office. Nevertheless, the lessor, as the provider of capital goods financing, has not returned the deed of the ship to its owner, even though the sale and lease-purchase agreement have been completed without any defects. The research questions addressed in this study are: 1. How is the implementation of the lease-purchase agreement for the Blue Star Tanker capital goods in Lease Agreement Number PPAF/PSGU-P/2014/VIII/133? 2. What is the basis for the lessor's possession of proof of ownership of the capital goods in the PPAF/PSGU-P/2014/VIII/133 agreement? This research employs a normative legal research method, which involves optimizing secondary data sources, including various primary legal materials, secondary legal materials, and tertiary legal materials. The primary data collection method used is a literature review. The research findings lead to the following conclusions: 1. The implementation of the lease-purchase agreement with Reference Number PPAF/PSGU-P/2014/VIII/133 does not meet the criteria for a lease-purchase agreement. The lease-purchase agreement with a clear option to buy states that the lessee will exercise the option to buy. This option to buy is provided at the end of the lease-purchase period. However, the legal ownership of the capital goods has been with the lessee from the outset when the ship sale agreement was registered with the harbor master's office on November 20, 2014, while the lease-purchase agreement ended in August 2017. 2. The legal basis for the lessor's possession of proof of ownership of the capital goods in Lease Agreement Number PPAF/PSGU-P/2014/VIII/133 is not valid. If based on ownership, the legal ownership documents are with PT. Sarana Multi Sejahtera as the lessee. If based on collateral rights, the lease-purchase agreement does not use the concept of collateral for the leased goods because the leased goods are actually owned by the lessee